2008
DOI: 10.1175/2007jcli1718.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Serial Dependence and Large-Scale Tropospheric Circulation on Midlatitude North American Terrestrial Carbon Dioxide Exchange

Abstract: Linear regression was used to relate modes of tropospheric circulation variability to estimates of gross ecosystem production (GEP) and ecosystem respiration (ER) measured at 14 midlatitude North American eddy covariance (EC) towers. The North Atlantic Oscillation (NAO) exhibited a north-south gradient in its effect on fluxes, with negative influence on fluxes at central and northeastern stations and positive influence on fluxes at southeastern stations. During spring, average values of GEP and ER within the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 84 publications
0
4
1
Order By: Relevance
“…All other significant correlations were not found with the carbon fluxes from our site. Although these studies in the literature and our study identified a relationship between local climate oscillations and carbon exchanges, differences in our findings and that of Grant et al [67], Hember and Lafleur [68] and Zhang et al [16] could be attributed to differences in geographic locations, hydrological conditions and different forest species. Our study found a significant link between climate oscillations and carbon fluxes, where local climate conditions were modified by the regional circulation in the Great Lakes region in eastern North America.…”
Section: Impacts Of Teleconnections On Carbon Fluxescontrasting
confidence: 94%
See 1 more Smart Citation
“…All other significant correlations were not found with the carbon fluxes from our site. Although these studies in the literature and our study identified a relationship between local climate oscillations and carbon exchanges, differences in our findings and that of Grant et al [67], Hember and Lafleur [68] and Zhang et al [16] could be attributed to differences in geographic locations, hydrological conditions and different forest species. Our study found a significant link between climate oscillations and carbon fluxes, where local climate conditions were modified by the regional circulation in the Great Lakes region in eastern North America.…”
Section: Impacts Of Teleconnections On Carbon Fluxescontrasting
confidence: 94%
“…Hember and Lafleur [68] investigated the connections between the NAO and the North Pacific Oscillation (NPO), another teleconnection pattern that is correlated with the ENSO, with surface air temperature, precipitation and carbon fluxes. Using eddy covariance flux data spanning 1994-2006 from mid-latitude North American ecosystems, they found that in the spring, correlation in the southeast stations was positive between NAO and surface air temperature, while the NPO was positively (negatively) correlated with temperature (precipitation) in the northeast.…”
Section: Impacts Of Teleconnections On Carbon Fluxesmentioning
confidence: 99%
“…Several reasons may be responsible for the differences. The large-scale circulation patterns have different effects on climate at the three sites due to their different geographic location (Table 1), and CO 2 exchange responds differentially with respect to latitude and climatic variations [e.g., Nemani et al, 2003;Gong and Ho, 2003;Notaro et al, 2006a;Hember and Lafleur, 2008;Grant et al, 2009;Wharton et al, 2009]. Another possible reason is that the three AmeriFlux research sites have different forest composition species, which affects the response of CO 2 exchange to the climate [e.g., Hadley et al, 2009;Richardson et al, 2009].…”
Section: Application Of the Methodology To Other Sitesmentioning
confidence: 99%
“…In this study, the annual NEE of deciduousdominated Harvard Forest and Morgan Monroe State Forest exhibits significant correlations with climate indices in fall, while conifer-dominated Howland Forest NEE is closely linked to climate indices in winter and spring. Other characteristics of sites such as hydrological conditions, topography, disturbance, nutrient, and measurement errors may also introduce some differences [Hember and Lafleur, 2008;Grant et al, 2009;Hadley et al, 2009]. Moreover, the study periods for the three sites are different, but in all cases, the data length is short.…”
Section: Application Of the Methodology To Other Sitesmentioning
confidence: 99%
See 1 more Smart Citation